Single subject research: Can a contextual approach to ratio material facilitate understanding of concepts for mentally retarded students? - Zahrina Salsabila; Dian Permatasari (12 Waiheru, 2024)
Mentally retarded children have weaknesses in learning that require understanding and memorization, one of which is in mathematics. The purpose of this study was to determine the effect of the contextual approach on material ratio values for mentally retarded students. The subjects of this study were students with mild mental retardation in class VII SMPN 15 Yogyakarta. This research method is a single-subject research design A-B. The research data collection technique is through documentation, interviews, and written tests. Data analysis in this study used analysis within conditions and analysis between conditions. The results of this study indicate that the average score obtained by mentally retarded students in the baseline phase is 32.5 and 95 in the intervention phase which is assisted by a contextual approach so that it is easy to understand the material. This shows that the contextual approach can have a positive influence in the form of increasing the ability to understand students' mental retardation concepts.